Инфильтрационные явления в условиях высокого давления при спекании кубического нитрида бора - Петруша, И.А.; Боримский, И.А.; Иценко, П.П.; Мельнийчук, Ю.А.; Цысарь, Т.А.; Никишина, М.В.; Ткач, В.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The peculiarities of the infiltration phenomena at HP-HT sintering of the CBN powders of
7–10 mkm particles sizes have been studied. The penetration of the impurities (O, Si, Al) in a sintering
body takes place from the Al2Si4O10(OH)2 (pyrophyllite) melt. The contamination of the sintered
material as a result of out-of-control infiltration adversely affects on its physicо-mechanical
properties.